Advokasi Isu Konservasi Arsitektur dan Kota melalui Seri Artikel Ilmiah Populer pada Situs Media Daring - Agustina, Sylvia; Dewi, Cut; Permatasari, Ulya Ananda; Ari, Al Asy; Qathrunnada, Shafira; Muthia, Fenita (Universitas Syiah Kuala, 2025)
The low level of public understanding about historical and architectural values of historical areas in both urban and rural areas often leads to neglect or even destruction of cultural heritage. This community service activity aims to increase public awareness of the importance of architectural and urban conservation through a service learning approach in the form of advocacy based on popular scientific writing in online media. To this end, the implementing team compiled and published four popular scientific articles that discuss conservation issues in communicative language and are tailored to the characteristics of general readers. The implementation method consists of three main stages: preparation (collection of materials, writing training), preparation and correction of articles, and publication and dissemination through various digital media. The results of the activity show that this strategy is able to reach a wider audience, encourage public discussion, and raise new awareness of the importance of preserving urban architecture. This activity also succeeded in positioning academic knowledge as an integral part of the media-based social advocacy movement. In the future, a similar approach is recommended to be expanded in scale with policy support and cross-sector collaboration.